The biology and macroparasites of the sixgill sawshark Pliotrema warreni - Foor, Brandon (Marine Research (MA-RE) Institute, 2017)
Thirty-two specimens of the sixgill sawshark, Pliotrema warreni, were trawled near Bird Island in Algoa Bay on the Eastern coast of South Africa in April and May 2015. The specimens were examined for anatomical proportions, reproductive characteristics, diet, and parasite assemblages. Several external measurements were collected including mass, total length, standard length, girth, rostrum length, interoccular to pre-caudal length, first dorsal origin to second dorsal origin, first dorsal origin to pre-caudal origin, and mouth width. The equation for mass (g) vs. total length (mm) was ln(Mass)=0.2997*ln(TL)+2.0383 for females and ln(Mass)=0.3321*ln(TL)+1.941 for males. 1st Dorsal to 2nd dorsal origin length (DD) to total length equations for females and males were DD=0.2451*TL-26.677 and DD=0.2598*TL-34.535, respectively. Mean lengths and masses were 11.5% greater and 50.3% heavier in females than males, respectively. Females were on average, 994 mm (759 mm – 1283 mm) in length while males were 891.8 mm (763 mm – 1015 mm). Average mass for females was 1702.5 g (602.5 g – 3478.5 g) whereas males it was 1132.6 g (687 g – 1593.5 g). Based on these data both sexes display isometric growth. Males were determined to reach sexually maturity around 850 mm which is similar to that reported by Ebert et al., (2013) around 830 mm. Females were found to reach sexual maturity at 1000 mm which is 100 mm smaller than what is reported by Ebert et al., (2013). Stomach mass increased with total mass and total length regardless of sex (female R² = 0.507; male R² = 0.213 for length and female R² = 0.6123; male R² = 0996 for mass). Females consumed larger prey items in terms of mass and length as well as a higher quantity of prey than males presumably because they are the larger sex and have an increased need for nourishment to provide for pregnancy. Prey items were redeye round herring, Etrumeus whiteheadi (64.96% of the diet), a benthic shrimp species not identified (7.69%), and Cape horse mackerel, Trachurus trachurus capensis (0.85%). Despite strict adherence to the guidelines for age determination for elasmobranchs provided in the literature, the conventional method used which involved extensive cleaning of the vertebral centra with an array of chemicals, setting and cutting in an epoxy resin, and staining for microscopy, did not yield readable results which could be used to determine the ages of these sharks. The highest abundance of parasites were found in the stomachs. Three specimens of a cymothoid isopod was found externally. Two specimens of Ascaris sp. nematode were found in the visceral cavity. The remaining 18 parasites consisted of three Neoechinorhynchidae sp. of acanthocephalan and 15 Proleptus obtusus nematodes all of which were found inside the stomachs. Given the results of the parasite survey, males and females do not have the same parasites as females have four different species while males only have one. More collections from other areas and times of year are necessary to obtain a better description of the species.